Public knowledge and awareness of diabetes mellitus, its risk factors, complications, and prevention methods among adults in Poland—A 2022 nationwide cross-sectional survey - Sękowski, Kuba; Grudziąż-Sękowska, Justyna; Pinkas, Jarosław; Jankowski, Mateusz (Frontiers in Public Health, 2022)
Regular monitoring of public awareness of diabetes is necessary to provide effective educational and preventive strategies. This study aimed to assess (1) public knowledge and awareness of diabetes among adults in Poland, as well as (2) to identify sociodemographic factors associated with public awareness of diabetes. This cross-sectional survey was carried out between 24 and 27 June 2022, on a non-probability random quota sample of 1051 adults in Poland. The questionnaire included ten questions related to the awareness of risk factors, symptoms, and complications of diabetes. Among the respondents, 10.5% had diabetes and 43.8% declared that they have a history of diabetes in their family. Only 17.3% of respondents declared a good level of knowledge of diabetes. Out of 10 symptoms of diabetes analyzed in this study, high blood sugar (80.7%) and chronic fatigue (74.6%) were the most recognized. Out of 8 diabetes risk factors analyzed in this study, overweight/obesity (80.4%) and unhealthy diet (74.1%) were the most recognized diabetes risk factors, while only 22.7% of respondents indicated tobacco use. The diabetic foot was the most recognized diabetes complication (79.8%), but approximately half of the respondents indicated vision problems (56.9%), kidney damage (52.1%), or cardiovascular diseases (50.2%) as diabetes complications. Female gender, having higher education and having a family member with diabetes were the most im-portent factors associated (p<0.05) with a higher level of awareness of diabetes. This study demonstrated insufficient public awareness of diabetes among adults in Poland. Gender and educational level were the most important factors significantly associated with the awareness of the selected aspects of diabetes, while self-reported financial situation and place of residence had none or marginal influence. The presented data manifest the importance of adopting a comprehensive education strategy regarding diabetes in Poland